New Structural and Single Nucleotide Mutations in Type I and Type II Collagens in Taiwanese Children With Type I and Type II Collagenopathies - Tsai, Meng-Che; Chou, Yen-Yin; Li, Chia-Yi; Wang, Yi-Chieh; Yu, Hui-Wen; Chen, Chia-Hsiang; Chen, Peng-Chieh (Frontiers in Genetics, 2021)
Collagenopathy is a rare genetic condition characterized by abnormality in either collagen structure or metabolism. Variations in its clinical presentations highlight diversity in the genetic causes and potential existence of concurrent mutations. Through whole exome sequencing (WES) complemented with multiplex ligation-dependent probe amplification, we identified the genetic etiologies for six cases with osteogenesis imperfecta (OI) in COL1A1 (p.T1298N, p.Q1280P, p.C1282AfsX48, and p.G557VfsX22) and COL1A2 (c.1-1677_133-441del) as well as three cases with spondyloepiphyseal dysplasia congenita in COL2A1 (p.G1041S, p.G654S, and p.G441A). Co-occurrence of COL1A1 and WNT1 mutations was found in a patient with a mild OI phenotype but severe osteoporosis. These findings extended the pathogenic variant spectrum of COL1A1, COL1A2, and COL2A1 for type I and type II collagenopathies. Although WES provides a fast and accurate method to identify the genetic causes in most of the patients with type I and type II collagenopathies, its limitation of detecting CNVs because of variable capturing uniformity should be kept in mind when interpreting the results. Taken together, we demonstrate that multiple genetic characterizing technologies can provide an accurate and efficient molecular diagnostic of new genetic variants in disease-causing genes that are compatible with clinical phenotypes.